Platelet deficiency disease among children and adolescents and measures to prevent it (Eurasian Medical Research Periodical, 2021)
This article discusses platelet deficiency disease among children and adolescents and measures to prevent it, as well as the health of adolescents, creating the necessary conditions for their full participation in society